(3ebGUO GdaMhds - (3Ydj GdSNhej , Ydj Hf UdGM GdOjf GdSNhejs ((3jhfS Hf ESeGYjd Hf GHQGgje GdMUfj GdOeTbi s)
(3ChdgG (B:s
(3NeSI OdGjd JOd Ydi EHWGd ePgH GdeNGdajf s
(3BNQgG (B:s
(3hEPG aQV GdYdi de jcf GdGLJgGO ebOhQkG adG jchf aQV caGjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B111s
Keywords: (3CUhd Gdabgs